2013
DOI: 10.1179/2042349713y.0000000019
|View full text |Cite
|
Sign up to set email alerts
|

Late-discovered petaloid monocotyledons: separating the native and alien flora

Abstract: The criteria that might help in assessing native or alien status are set out and any recent developments noted. The major change has been a better understanding of north-western European distribution and alien plant occurrences, mainly through the production of dot-map floras. Six petaloid monocotyledons are examined -all well-known and long-grown garden plants, and all with not only a late discovery, but also with a subsequent almost immediate clumping of records from a number of counties. This is contrasted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…in Maudfields’ in Middlesex (Pearman, 2007). By the 1820s, it had been recorded from meadows in a further five counties but most tellingly the largest populations in Wiltshire, most notably North Meadow, were not discovered till the 1880s (Pearman, 2013; Walker, 2021). This seems remarkably late for such a conspicuous and attractive species and has led many botanists to the conclusion that it was simply not present in the wild before the eighteenth century by which time the vast majority of native British plant species were first recorded.…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…in Maudfields’ in Middlesex (Pearman, 2007). By the 1820s, it had been recorded from meadows in a further five counties but most tellingly the largest populations in Wiltshire, most notably North Meadow, were not discovered till the 1880s (Pearman, 2013; Walker, 2021). This seems remarkably late for such a conspicuous and attractive species and has led many botanists to the conclusion that it was simply not present in the wild before the eighteenth century by which time the vast majority of native British plant species were first recorded.…”
Section: Historymentioning
confidence: 99%
“…Although F. meleagris is an iconic species of ancient floodplain hay meadows in Britain, its native status has been the subject of much debate. A recent account on the genetic diversity of the European populations (Day, 2017) did not provide conclusive proof either way and so the most recent flora of the British Isles (Stace, 2019) listed it as 'doubtfully native' although some botanists have argued strongly for it to be classed as modern introduction (neophyte; Leach, 2010Leach, , 2019Pearman, 2007Pearman, , 2013Walker, 2021). The current lack of direct evidence means that a final judgement on its status may be premature and may have to await more conclusive genetic results.…”
mentioning
confidence: 99%
“…Others cite the lack of references to it in literature, art, architecture, local folklore and placenames and its absence from the fossil record (Godwin, 1976;Pennington, 1977). Weighing up arguments on both sides Pearman (2007Pearman ( , 2013 concluded that it was most likely an ornamental introduction to monastic gardens that escaped to colonise semi-natural habitats in the eighteenth century, especially in the vicinity of Swindon and Oxford.…”
Section: Introductionmentioning
confidence: 99%